Allergic Rhinitis in Childhood and the New EUFOREA Algorithm - Scadding, Glenis Kathleen; Smith, Peter Kenneth; Blaiss, Michael; Roberts, Graham; Hellings, Peter William; Gevaert, Philippe; Mc Donald, Marinda; Sih, Tania; Halken, Suzanne; Zieglmayer, Petra Ursula; Schmid-Grendelmeier, Peter; Valovirta, Erkka; et al. (Frontiers in allergy, 2021)
Allergic rhinitis in childhood has been often missed, mistreated and misunderstood. It has significant comorbidities, adverse effects upon quality of life and educational performance and can progress to asthma or worsen control of existing asthma. Accurate diagnosis and effective treatment are important. The new EUFOREA algorithm provides a succinct but wide- ranging guide to management at all levels, based on previous guidelines with updated evidence and has been adjusted and approved by experts worldwide.